Dude Looks Like A Lady: Straight Camp and the Homo-social World of Hard Rock. - Jack Burton (University of Edinburgh, 2007)
Madison Square Garden. 1973. Robert Plant, the 25 year old singer and frontman of Led Zeppelin, undoubtedly the world's biggest rock band, takes to the stage in front of another sell out crowd. He is dressed in his trademark outfit of blue denim jeans and snakeskin boots. His torso is conspicuously left uncovered beneath a blue shirt several sizes too small. His muscular biceps are hugged by its gathered sleeves, presumably worn with the intention of creating a sense of oriental opulence but actually suggesting nothing more exotic than a woman's blouse. As he flicks aside his lustrous mane of blond curls he delivers the opening lines of Black Dog in his trademark high-pitched wail; "Hey, hey, mama. Said the way you move. Gonna make you sweat. Gonna make you groove."